Implementation of Moral Education through Local Wisdom Values at Syeikh Abdurauf Integrated Islamic Kindergarten - Mariana, Siti; Juwita, Rani Puspa (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
Moral education is an effort or activity in fostering the personality of students to a better level, be it in the dimension of knowledge, creativity, morals, and personality through local wisdom values. This study aims to find out how the implementation of moral education is carried out effectively through the application of local wisdom values in Sheikh Abddurauf IT Kindergarten. This study uses a descriptive qualitative research method, while the data collection technique in this study is using interview and documentation techniques. And the techniques in data analysis in this study use the Miles and Huberman techniques, namely data reduction, data display and conclusion drawing. The results of this study show that the methods used in learning the implementation of moral education through local wisdom values have been effective and have been applied in the curriculum and daily life.┬á┬á